Peningkatan Kreativitas dan Hasil Belajar Matematika Siswa Kelas V dengan Menggunakan Strategi Creative Problem Solving di Sekolah Dasar - Tita Purnama Sari; Zulfa Amrina; Daswarman Daswarman (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
This research was trigerred by the lack of students’ creativity in solving problems. It has been seen from the lack of students’ curiosity. The students had no desire to find and research, to try finding broad and satisfactory answers, rarely respond to questions raised and rarely give more answers, less enthusiasm in asking questions and examining the questions given by the teacher. The purpose of this study was to describe the creativity and learning outcomes of students in learning Mathematics using the strategy of Creative Problem Solving in class V State Elementary School 10 Koto Baru, Solok District. The type of research was a classroom action research. This study was conducted in two cycles, each cycle consisting of two meetings and one final test cycle. The subjects of this study were the students of class V State Elementary School 10 Koto Baru, around 18 people. The research instruments applied were observation sheet of students' creativity, observation sheet of teaching activity, test of student learning result. Based on the result of observation about students’ creativity in cycle I and II, the creativity percentage in cycle I was 51,1% and increase to 70,55% in cycle II. Based on the results of the study, the percentage of students who achieved mastery learning in the first cycle 50% and increased in cycle II to 72%. This meant that learning Mathematics by using Creative Problem-Solving strategy could improve creativity and learning outcomes of grade V students of State Elementary School 10 Koto Baru. Based on the results of this study, researchers suggested that teachers could use Creative Problem-Solving strategies in learning to improve creativity and students’ learning outcomes.